Analysis of The Impact of The Covid-19 Pandemic on The Performance of Indonesian Non Oil and Gas Exports - I Gusti Bagus Ngurah Diksa; Dewa Ayu Srijayanti (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
In 2020, Indonesia's exports decreased by 2.61 percent due to declining global and domestic demand during the COVID-19 pandemic. The decline in exports was not too deep due to the increase in non-oil exports by 16.73 percent, while non-oil exports fell by 10.10 percent. This shows the potential for non-oil exports to support the Indonesian economy during the pandemic. Seeing the impact of COVID-19 on export performance then used the ARIMA method. Based on the research, it was found that at the beginning of the COVID-19 pandemic, Indonesia experienced a slump in export performance, especially non-oil and gas. This is due to various policies regarding restrictions on mobility.